DEVELOPMENT OF SOLID SELF-MICROEMULSIFYING DRUG DELIVERY SYSTEM OF DIACEREIN FOR ENHANCED DISSOLUTION RATE - TAMBOLI, JAMEER A; K MOHITE, SHRINIVAS (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the present study was to develop solid self-microemulsifying drug delivery system (S-SMEDDS) of diacerein (DCN) for enhancement of dissolution rate. Methods: Three batches of liquid SMEDDS were prepared using oleic acid, Tween 80, and polyethylene glycol 200 as oil, surfactant, and cosurfactant, respectively. Microemulsion region was recognized by constructing a pseudoternary phase diagram containing a different proportion of oil, surfactant, and cosurfactant. Prepared liquid SMEDDS was evaluated for thermodynamic stability study, dispersibility tests, globule size, zeta potential, and viscosity. Liquid SMEDDS was then converted to S-SMEDDS by adsorption technique using Neusilin US2 as a solid carrier. Prepared S-SMEDDS was evaluated for different micromeritic properties, drug content, reconstitution properties, in vitro dissolution study, Fourier transform infrared, and scanning electron microscopy. Results: The results showed that all batches of liquid SMEDDS were found to be thermodynamically stable. Reconstitution properties of S-SMEDDS showed spontaneous microemulsification with globule size 0.271 μm and −16.18 mV zeta potential. From the results of in vitro dissolution study, it was found that the release of DCN was significantly increased as compared with plain DCN. Conclusion: The study concluded that dissolution rate of poorly water-soluble drug like DCN can be increased by developing S-SMEDDS formulation.